Building an Open Sharing Platform for ELT Courses: The Example of MOOC Network - Na Li; Yitian Zhang (Advances in Multimedia)
English language teaching (ELT) has become an essential and indispensable part of primary education in today’s increasingly frequent international exchanges, and MOOC, as a massive online teaching model integrating content and learning support services, is leading a pedagogical transformation, providing a historic opportunity to build an open sharing platform for ELT. However, developing an open sharing platform around MOOC networks is still challenging, especially for English courses, where various course designs significantly increase the difficulty of tracking students’ learning status. Therefore, we introduce RNN-based sequence-to-sequence knowledge tracing models as the software foundation of the shared platform. The transformer model is further chosen to simulate students’ historical learning trajectories to solve the problem of long-term dependency in traditional models. The research results have important theoretical and practical implications for building an open sharing platform for ELT courses.